Strategic Leadership of School Admministrators as Perceivedby Teachers in Welfare Schools Group 1 under the Bureauof Special Education Administration - Kamwon, Kaewta; Pauwongsakul, Saroch (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to study and compare strategic leadership of school administrators as perceived by teachers in welfare schools group 1 under The Bureau of Special Education Administration classified by sex and work experience. The sample consisted of 171 teachers in welfare schools group 1, obtained by stratified random sampling according group of schools. The research instrument was a five-level rating scale questionnaire with content validity 1.00 and a reliability of 0.99. The statistics used in the data analysis were percentage, mean, standard deviation, t-test one-way analysis of variance and test the pairwise mean difference by Scheffe's method with a statistical significance level at 0.05 The findings were as follows: 1. The strategic leadership of school administrators as perceived by teachers in welfare schools group 1 under The Bureau of Special Education Administration, was overall and in each individual aspect were a high level, ranking in the order of mean from high to low as vision, revolutionary way of thinking, the ability to bring various inputs to determine strategy, aspects of having expectations and creating opportunities for the future, and high level cognitive. 2. The strategic leadership of school administrators as perceived by teachers in welfare schools group 1 under The Bureau of Special Education Administration classified by sex, was overall and in each individual aspect, there was no tstatistically significant difference level. 3. The strategic leadership of school administrators as perceived by teachers in welfare schools group 1 under The Bureau of Special Education Administration classified by work experience, was overall and in each individual aspect, there was no statistically significant difference.